2018
DOI: 10.3389/fphys.2018.01507
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Role of Placental Aquaporins and the Pathogenesis of Preeclampsia

Abstract: Accumulated evidence suggests that an abnormal placentation and an altered expression of a variety of trophoblast transporters are associated to preeclampsia. In this regard, an abnormal expression of AQP3 and AQP9 was reported in these placentas. Recent data suggests that placental AQPs are not only water channel proteins and that may participate in relevant processes required for a normal placental development, such as cell migration and apoptosis. Recently we reported that a normal expression of AQP3 is req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Spzilbarg et al suggested that the absence of AQP9 functionality may impair the lactate transfer, promote more ROS accumulation, and increase the hST apoptosis, triggering apoptotic syncytial aggregate release into maternal circulation producing systemic endothelial dysfunction in preeclampsia. 17 Our study showed that the mean serum concentration of AQP9 was greater in women with early-onset preeclampsia (722.22 AE 211.80 pg/ mL) than in the control group (499.97 AE 68.89 pg/mL, p < 0.001). We think that this result conclusively demonstrated the inflammation in the pathological process of early-onset preeclampsia.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Spzilbarg et al suggested that the absence of AQP9 functionality may impair the lactate transfer, promote more ROS accumulation, and increase the hST apoptosis, triggering apoptotic syncytial aggregate release into maternal circulation producing systemic endothelial dysfunction in preeclampsia. 17 Our study showed that the mean serum concentration of AQP9 was greater in women with early-onset preeclampsia (722.22 AE 211.80 pg/ mL) than in the control group (499.97 AE 68.89 pg/mL, p < 0.001). We think that this result conclusively demonstrated the inflammation in the pathological process of early-onset preeclampsia.…”
Section: Discussionmentioning
confidence: 44%
“…As preeclampsia is a complex disease resulting from many concurrent mechanisms, AQP9 was considered to contribute as part of pathogenesis that gives rise to the diverse clinical signs of this disease. 17 To the best of our knowledge, no study to date has assessed circulating levels of AQP9 in preeclamptic patients. This study aimed to evaluate maternal serum AQP9 concentrations of pregnant women complicated with early-onset preeclampsia and compare them with the uncomplicated control group with normal blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding AQP3, we recently reported that this protein was considerably decreased in preeclamptic placentas (Szpilbarg & Damiano, 2017). Although these changes in AQP3 and Cav-1 were found at the end of the preeclamptic gestation and in VT cells, we propose that the abnormal expression of both proteins could take place during the first stages of differentiation of the trophoblast stem cells and persist after their subsequent differentiation in extravillous and VT affecting both lineages (Szpilbarg et al, 2018).…”
Section: Aqp3 Colocalizes With Cav-1mentioning
confidence: 82%
“…Thus, any alteration in NADH production may give rise to ROS accumulation triggering cell damage and finally leading to cell death (Miki et al, 2013). In this regard, there is considerable evidence that ROS promotes the apoptotic death of villous trophoblasts (Szpilbarg et al, 2016(Szpilbarg et al, , 2018Marín et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, functional experiments showed that water and monocarboxylate transport mediated by AQP9 were dramatically reduced ( Damiano et al, 2006 ). Notwithstanding this, there is no evidence of alterations in the transcellular water transport between the mother and the fetus, suggesting that the main role of AQP9 in the human placenta is not related to water transport ( Szpilbarg et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%